DINÂMICA DA SERRAPILHEIRA EM DIFERENTES FITOFISIONOMIAS NO LESTE SUL-MATO-GROSSENSE - VINICIUS GEROLIN CEBALLOS (2024)
This study aimed to investigate the particularities of two phytophysiognomies, the Cerrado Denso and the Mata de Galeria, in the municipality of Três Lagoas, located in the eastern part of Mato Grosso do Sul, using leaf litter as a diagnostic tool to assess the environmental quality of these ecosystems. From a geosystemic perspective, based on Landscape Geoecology, the research adopted an integrated approach that considers the complex interactions between the physical, biological, and anthropic elements that make up these landscapes. Throughout the work, the production, stock, decomposition, and water retention capacity of the leaf litter were analyzed, with special attention to seasonal variations and the specific characteristics of each phytophysiognomy. Each of these analyses is explored in specific chapters of the study, where detailed methodologies are presented, suitable for each of the proposed objectives. The results showed that the average monthly leaf litter production varied significantly between the studied areas, revealing that the structural distinction between the phytophysiognomies was a determining factor for these variations. In some regions, the observed scenario differed from what was expected, with similar vegetation presenting distinct production depending on their locations. In the Cerrado Denso, production was more intense during the dry season, favored by more severe climatic exposure, while in the Mata de Galeria, production was more stable throughout the year, reflecting more protected and humid environmental conditions. The water retention capacity of the leaf litter also varied between the phytophysiognomies. In the Cerrado Denso, the leaf litter demonstrated the ability to absorb up to 193% of its weight in water, thanks to the morphology of its leaves, which have smaller but thicker blades, reducing evapotranspiration and favoring moisture retention between its layers, even in conditions of lower water availability. This process is crucial for maintaining soil moisture and fertility, as well as influencing nutrient stock dynamics and the resilience of these environments to ecological disturbances, such as large-scale fires. In drier environments, such as the Cerrado Denso, leaf litter decomposition occurred more slowly due to the lower water availability and greater dependence on climatic factors. This reinforces the importance of leaf litter not only as a regulator of soil moisture but also as a key factor in the adaptation of these vegetations to more adverse environmental conditions. This comparative analysis highlighted leaf litter as a sensitive indicator of environmental quality, reflecting the adaptability of these vegetations to local climatic conditions, but also their vulnerability to disturbances, such as prolonged droughts and fires. Understanding these dynamics is essential for the preservation and proper management of these environments. The study emphasizes that well-structured management actions can prevent ecosystem degradation and ensure the maintenance of essential ecological functions in both the Cerrado Denso and the Mata de Galeria, which are fundamental for the sustainability and resilience of the Cerrado biome.